LOOKING BEYOND TRADITIONAL ENTREPRENEURSHIP: DECODING THE ROLE OF ACCESS TO FINANCE, BUSINESS SUPPORT, SAVINGS PRACTICES, AND SKILL DEVELOPMENT FOR WOMEN AGRO-ENTREPRENEURS - Singh, Shivendra; Kumari, Priyanka (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Services provided by microfinance institutions are becoming widely recognized as effective means of ending poverty and empowering women. Nonetheless, fewer women than men operate and handle businesses in many parts of the world. This research examines how agro-women’s business growth in Bihar, India, is affected by microfinance services. A standardized five-point likert scale questionnaire was used to gather data from 240 respondents, SPSS 21 and AMOS 23 were used for analysis. In order to evaluate the concept validity and measurement reliability, confirmatory factor analysis was done. The theories on the impact of microfinance institutions on agro-women’s entrepreneurial growth were formerly tested using a structural equation model. The study’s findings revealed a positive and significant impact of access to finance, savings, and business support, although there is a need for improvement in skill development for agro-women entrepreneurs.